Comprehensive mental health and psychosocial support for war survivors at Chenna Kebele, Dabat woreda, North Gondar, Ethiopia - Niguse Yigzaw; Tewodros Hailu; Mekides Melesse; Ashenafi Desalegn; Haymanot Ezezew; Tebaber Chanie; Goshu Nenko; Moges Tesfahun; Simegn Sendek; Seblewongel Tinsae (BMC Psychiatry, 2023)
Abstract Background Armed conflict and natural disasters cause serious psychosocial problems. Providing comprehensive bio-psychosocial support to the community after a war, traumatic, or devastating event has a significant impact on community reconstruction and resilience. As a result, the goal of this project was to conduct community diagnosis, identify individuals experiencing psychological distress, and provide comprehensive mental health and psychosocial support for the Chenna Kebele population in Dabat Woreda, North Gondar, Ethiopia. Methods A mixed research approach, specifically an explanatory study design, was used to assess psychosocial issues among war survivors. In-depth interviews, focus group discussions, and observation were used to assess the psychosocial and economic consequences of the war on survivors. Additionally, a structured questionnaire was employed to assess mental health problems among the target population. The project was conducted in three phases. Result A total of 550 households were assessed using a structured questionnaire. Of them, 45 people reported a range of mental health issues, including post-traumatic stress disorder (PTSD), major depressive disorder (MDD), adjustment disorder, protracted bereavement disorder, and insomnia. PTSD is the most common diagnosis, accounting for 38 cases. Four cases of major depressive disorder, three cases of prolonged grief, and two neurologic cases were also identified during the screening. Females had a higher number of PTSD cases as compared with males. Fifteen women reported sexual violence, and the number may be high because of underreporting and refusal to disclose the situation. The result also indicated significant property damage, loss of life stocks, and disengagement from basic services like water. Intervention with follow-up was provided at the individual, group, and community levels in order to reverse the devastating situation. The intervention included pharmacotherapy, psychotherapy, and social networking. Conclusion and recommendation Overall, the community has experienced multiple psychosocial and economic problems. Hence, providing holistic mental health psychosocial support, clearing the site and burying the dead body, and re-initiating the terminated social gathering event will alleviate the existing problem and create a resilient community.